VERBA MEMUKUL DALAM BAHASA BALI KAJIAN METABAHASA SEMANTIK - Saputra, I Made Dian (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
Balinese language as Balinese Lingua franca still has rules in speaking. There many Balinese words that are not familiar even neglected in this era, one ofÂ  those is verb. There are many verbs in Balinese, but researcher just wants to focus on one verb, that is ngetok seen from metalanguagenatural semantics. The verb ngetok has 32 similar meanings as follows; â€œngebug, ngedig, nigtig, ngupek, magambel, mugpugin, mukpukin, ngukul, nungting, ngempug, nyakcak, noktok, ngeplokin, nebuk, ngaasin, nepung, ngintuk, ngalocok, namplak, nyemÃ©s, nempÃ©lÃ©ng, nyagur, nyepÃ©din, nglamet, ngamplongin, ngamplengin, ngemplangin, nglentangin, ngaplekin, nyontok, nylimed andÂ  mentil.â€ From the whole verb forms of â€œngetokâ€ there are differences of each form seen from the wat of hitting related to the device used to hit, subject and object being hit. Verb in Balinese has to different meanings, that can be explained by explication technique of X does something on Y, something good or bad happens on Y. The difference of meaning was gained from the analysis of original meaning with uncomposed polysemi.